Optical and Electrical Characterization of ZnO:Ga₂O₃ Thin Films Synthesized by MASP for Oxygen Gas Sensor Applications - Sulhadi,; Hendra Dwi Gunawan,; Putut Marwoto,; Sugianto,; Fristian Rifita,; Hendi Prawiro Raharjo,; Agus Nu'man, (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2025)
This study investigates the effect of oxygen (O₂) exposure on the optical and electrical properties of ZnO:Ga₂O₃ thin films synthesized by the Microwave-Assisted Spray Pyrolysis (MASP) method. A 3% Ga₂O₃ doping level was used as the optimal composition to enhance the film’s stability and conductivity. After deposition and annealing at 450 °C, the films were exposed to O₂ gas at pressures ranging from 0 to 400 mTorr to evaluate their oxygen detection capability. Optical properties were characterized using UV–Vis spectroscopy, while electrical measurements were performed with an IV-meter employing the two-point probe method. The results show that the optical band gap increased from 3.19 eV to 3.23 eV with rising O₂ pressure due to the Burstein–Moss effect, indicating a shift of the Fermi level and carrier concentration change upon oxygen adsorption. Simultaneously, the electrical resistance increased from 1.05 × 10⁷ Ω to 1.25 × 10⁷ Ω, attributed to the formation of a surface depletion layer that reduces the density of free carriers. In addition, the sensitivity increased from 1.90% at 100 mTorr to 19.05% at 400 mTorr, indicating an increasingly pronounced electrical response with increasing oxygen pressure. The positive correlation between band gap and resistance confirms that oxygen exposure directly affects the film’s optoelectronic behavior. With high transparency, structural stability, and linear response to oxygen, the ZnO:Ga₂O₃ thin film demonstrates strong potential for real-time oxygen sensing applications.